Genesis of State Social Policy of Ukraine: Administrative and Legal Aspect - Katsalap, L. S. (Law and Safety, 2020)
The author of the article studies and systematizes the set of available scientific achievements on the origin, formation and development of state social policy of Ukraine, considering the fact that one of the priorities of Ukrainian society in the need for progressive improvement of all mechanisms of public administration is the formation of effective social policy. And taking into account the aggregate of the most urgent issues of the development of our state, connected with overcoming the negative phenomena in a social life, the administrative and legal provision of the reliable mechanism of social protection of the population by public authorities requires particular attention. The author of the research analyzes the historical and legal base of the social sphere of the Ukrainian state since the adoption of the Declaration of State Sovereignty of Ukraine until now. It is emphasized that international legislation aimed at ensuring human rights and freedoms became the basis of regulatory and legal provision of the social sphere in Ukraine. It is noted that the analysis of the content of social functions of the Ukrainian state is characterized by the presence of factors of democratic state formation in the society that is focused on the European vector. The author followed the chronological sequence of the formation of social institutions and legislative regulation of social relations in the state, which led to the current state of social policy. The difficult way of the formation of modern social policy of Ukraine, its achievements, weaknesses and perspective directions of the development are highlighted. The author defines the priority directions of future scientific researches in the specified sphere.